2021
DOI: 10.1021/acs.jmedchem.1c00318
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Methoxy-, Methylenedioxy-, Hydroxy-, and Halo-Substituted Benzophenanthridinone Derivatives as DNA Topoisomerase IB (TOP1) and Tyrosyl-DNA Phosphodiesterase 1 (TDP1) Inhibitors and Their Biological Activity for Drug-Resistant Cancer

Abstract: As a recently discovered DNA repair enzyme, tyrosyl-DNA phosphodiesterase 1 (TDP1) removes topoisomerase IB (TOP1)-mediated DNA protein cross-links. Inhibiting TDP1 can potentiate the cytotoxicity of TOP1 inhibitors and overcome cancer cell resistance to TOP1 inhibitors. On the basis of our previous study, herein we report the synthesis of benzophenanthridinone derivatives as TOP1 and TDP1 inhibitors. Seven compounds (C2, C4, C5, C7, C8, C12, and C14) showed a robust TOP1 inhibitory activity (+++ or ++++), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…The TDP1 inhibition was tested through a fluorescence assay according to a previously reported method [ 29 ]. Detailed procedures are included in the Supporting Information .…”
Section: Methodsmentioning
confidence: 99%
“…The TDP1 inhibition was tested through a fluorescence assay according to a previously reported method [ 29 ]. Detailed procedures are included in the Supporting Information .…”
Section: Methodsmentioning
confidence: 99%
“…The following are available online at, NMR 1 H and 13 C, HRMS of benzyloxy-DCA derivatives (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19); Table S1. The influence of the deoxycholic acid derivative 8 at 10 µM on topotecan cytotoxicity; Table S2.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Several studies have reported the development of TDP1 inhibitors of organic chemical matter [ 6 , 7 , 8 , 9 ] as well as natural product derivatives: steroids ( A – C ) ( Figure 1 ) [ 10 , 11 , 12 ], coumarins [ 13 , 14 ], usnic acids [ 15 , 16 , 17 , 18 , 19 ], and aminoadamantanes containing monoterpene-derived fragments [ 20 , 21 , 22 , 23 ]. Known TDP2 inhibitors are represented by isoquinoline-1,3-diones ( J ) [ 24 ], deazaflavins ( E ), and toxoflavins ( F ) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although some CPT-type Top1 inhibitors have been applied clinically, they still suffered from disadvantages such as poor chemical stability, drug resistance, gastrointestinal toxicity or serious side effects [ 7 , 10 ]. Consequently, in the past decades many investigations have focused on the discovery and development of novel non-CPT Top1 inhibitors [ 11 , 12 , 13 ]. It has been reported that several non-CPT Top1 inhibitors including the indenoisoquinolines LMP400 (indotecan), LMP776 (indimitecan) and LMP744 ( Figure 1 ) have been used in clinical trials [ 14 ].…”
Section: Introductionmentioning
confidence: 99%